Estratégias de Coping e Síndrome de Burnout em estudantes universitários: papel da vinculação aos pais e pares - Azevedo, Solange Alexandra Matos (2020)
According to the attachment theory, the attachment relationships experienced with parents as a secure base, allow that the individual throughout his life refer to internal models, wich are being reorganized to face with adverse situations in an adaptive manner. Safe attachment to parents and the adaptation to adverse situations may be a protective factor against the experience of Burnout. The main goal of this study is to analyse the effect of attachment to parents in the development of Burnout syndrome in young adults, being also tested the mediating effect of the development of coping strategies in the previous association. The sample consisted of 1089 subjects of both genders, aged between 18 and 25 years. The assessment tools used were a sociodemographic questionnaire and self-report instrument, namely the Father and Mother Inquiry Attachment (QVPM), The Burnout Inventory and The Cope Inventory. The results suggested that the perceived attachment to parents has a predictive effect on the Burnout experience, and that coping strategies have a mediation effect on the previous association. The results will be analyzed according to the attachment theory, considering parenting attachment, as well as the effect of coping strategies in adapting to academic life and experience of Burnout in young adults.